Ethanol and Methanol Levels in The Oplosan Liquor - Angki Purwanti; Ni Putu Aryadnyani (Poltekkes Kemenkes Jakarta III, 2020)
Oplosan liquor is one form of illegal drink that is often found in police raids in various areas. The purpose of this study was to determine the ethanol and methanol levels in mixed liquor obtained from the results of the Sector Police raids in Cipayung District, East Jakarta, in 2017. This study was a cross-sectional descriptive study. Determination of ethanol and methanol levels is done by gas chromatography at the Daerah Khusus Ibukota Jakarta Health Laboratory. The sample in this study amounted to 14 samples. Based on the research obtained Ethanol content from test material (10.08-50.14)% v/v with an average (28,39±15,09)% v/v and methanol content is (0.08-2.04)% v / v with an average of (0,81±0,72)%v/v. Samples whose ethanol content is equivalent to alcoholic groups A, B, and C are 0%, six bottles (42.86%), and eight bottles (51.13%). All samples contained methanol with levels> 0.01% and were not packaged according to the requirements of the Regulation of the Indonesian Food and Drug Supervisory Agency No. 14/2016 (BPOM). It is suggested to do a follow-up in counseling related to mixed alcohol, especially for adolescents in this area. Further research is suggested to identify illegal drugs in the confiscated alcoholic drinks from this area. It is recommended to the Cipayung District Police to clean the area from mixed alcohol.